Training of information retrieval in the State university of Vilnius: some contential and technological aspects of education in the field of librarianship and bibliography - Prokopčik, Marija (Knygotyra, 1990)
The article deals with the problem of professional education of librarians at the University of Vilnius. The changing role of information, which is becoming one of the natural resources of the country, and the rapid development of computer technology reveal new professional demands for librarians. As a result of this tendency, teaching online bibliographical searching has become of great importance in the library education curriculum.Specific conditions of development and practical needs of libraries and information services, main traits, and opportunities of higher education in Lithuania are revealed. This makes it possible to create an original conception of automated information retrieval training. The problems of information retrieval are studied in subjects such as Librarianship, Bibliography, Information Retrieval Systems, Information, and Technical Aids for Library Work, which are based on a specially created training automated information retrieval system (AIRS).Three different kinds of connections between the revealed subjects are presented in a scheme and commented upon.The choice of education technology is discussed. The main forms are various practical studies, realized on the basis of AIRS. These also help overcome the psychological barrier that arises when working with computers.
Keywords: -